Acidogenic fermentation of food waste in a leachate bed reactor (LBR) at high volumetric organic Loading: Effect of granular activated carbon (GAC) and sequential enrichment of inoculum. (October 2022) - Radadiya, Pooja; Lee, Jango; Venkateshwaran, Kaushik; Benn, Nicholas; Lee, Hyung-sool; Hussain, Abid
Graphical abstract: Highlights: LBR operation at high volumetric loading was demonstrated. GAC loading and inoculum enrichment significantly impacted the reactor performance. Optimized GAC loading resulted in high acidogenic yields of 507 gCOD/ kg VSadded. Inoculum Enrichment improved the acidogenic yields to 617 gCOD/ kg VSadded. Butyrate was the primary short chain fatty acid at high GAC loading. Inoculum enrichment did not impact the composition of short chain fatty acids. Abstract: This study investigated the impact of different granular activated carbon (GAC) loadings and inoculum enrichment on acidogenic fermentation of food waste in a leachate bed reactor (LBR) operated at a high volumetric organic loading of 49 g VS/Lreactor . LBR with a high GAC loading of 0.51 g GAC/g VSfood waste achieved hydrolysis yield of 620 g SCOD/kg VSadded, significantly (P ≤ 0.05) higher to that obtained for LBRs with low or no GAC loading. A high GAC loading also resulted in a higher acidification yield of 507 g CODSCFA /kg VSadded . Butyrate dominated the short-chain fatty acid (SCFA) composition by constituting 57–60 % of total SCFA at high GAC loadings, while the composition of acetate (38–40 %) and butyrate (36–38 %) were similar at lower GAC loadings. Inoculum enrichment further improved the hydrolysis and acidogenesis yields by 10–22 % resulting in the final hydrolysis yield of 683 g SCOD/kg VSadded and acidification yield of 617 g CODSCFA /kg VSadded .